HIJRAH DALAM PERSPEKTIF SOSIO-KULTURAL HISTORIS - Said, Hamka (Hunafa: Jurnal Studia Islamika, 2005)
The event of hijrah (migration) has a number of sociological, cultural, even economical reasons as backgrounds. The antipathetic attitude of the polytheists (the Quraish) to Muhammad and his followers is not only because of theological factor but also of the implication of the intended theological dimension to their social, cultural and economic lives. The invitation of Yathrib people to Muhammad and his followers to migrate to Madinah is likewise basically more motivated by socio-cultural and historical elements than normative theological ones.           Kata kunci:  Hijrah, sosio-kultural historis